Pengaruh Program Bank Sampah Terhadap Kondisi Sosial Ekonomi Dalam Situasi Covid-19 - Nurul Hidayah; Nining Latianingsih; Titik Purwinarti (Administratif Profesional, 2022)
This study aims to determine the partial effect of the waste bank program on the socio-economic conditions of the partner customers of the Rumah Harum Garbage Bank. In addition, this research is expected to be a consideration for waste bank managers, especially the Rumah Harum Garbage Bank and partners in paying attention to the waste bank program that will be created. Thus, the socio-economic conditions of partner customers can continue to improve. This study is a descriptive study with a quantitative approach with a population of 195 partner customers. The sample calculation uses the slovin formula, so the number of samples used is 66 respondents with the sampling technique using Cluster Sampling. Testing the instrument using validity and reliability tests. While the data analysis method used simple linear regression analysis, the coefficient of determination R² test, and the T test. Data processing in this study used SPSS 22 software for windows. The regression equation model obtained Y = 7.774 + 0.086x is feasible to use. Based on the results of the partial correlation test, the waste bank program variable (X) has an influence on the socio-economic condition variable (Y) of 49.5%. Based on the results of the analysis of the coefficient of determination (R2), the result is 49.56% socio-economic conditions are influenced by the waste bank program while the remaining 50.44% is influenced by other variables not discussed in this study.